What is athlete life management in Singapore's sporting ecosystem? An interpretative phenomenological analysis of a dual-career assistance program. Issue 6 (2nd November 2022) - Chambers, Timothy; Lim, Harry
ABSTRACT: This investigation explored practitioners' experiences of providing Athlete Life Management (ALM) as a career assistance support service for Singaporean athletes. The researchers adopted a relativist ontology and constructionist epistemology to frame the study, and an interpretative phenomenological analysis methodology. The five participants (four female, one male) were from various Singaporean sporting organisations and were employed as ALM practitioners. Following data analysis, we discovered one superordinate theme: sporting ecosystem. Three higher order themes were also identified within the sporting ecosystem: cultural evolution towards a sporting identity, harmonious practitioner engagement, and practising with care and compassion. Collectively, the results emphasised the organic development of ALM, and that this important athlete support service is situated within Singapore's dynamic sporting ecosystem. The study adds valuable knowledge to the existing literature on athlete career support by highlighting the practitioners' experiences within a non-traditional discourse.